2016
DOI: 10.1007/s00441-016-2469-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34b/c inhibits aldosterone-induced vascular smooth muscle cell calcification via a SATB2/Runx2 pathway

Abstract: Increasing evidence shows that aldosterone and specific microRNAs (miRs) contribute to vascular smooth muscle cell (VSMC) calcification. In this study, we aim to explore the mechanistic links between miR-34b/c and aldosterone in VSMC calcification. VSMC calcification models were established both in vitro and in vivo. First, the levels of aldosterone, miR-34b/c and special AT-rich sequence-binding protein 2 (SATB2) were measured. Then, miR-34b/c mimics or inhibitors were transfected into VSMCs to evaluate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…23 MR activation has been shown to promote the expression of genes involved in MR-dependent vascular remodelling and calcification in VSMCs, such as collagens I and III, the integrin alpha-5 subunit, IL-16 and cytotoxic T-lymphocyte antigen-4 for vascular remodelling and genes associated with vascular calcification, such as alkaline phosphatase, parathyroid hormone receptor-2 and bone morphogenetic protein-2. 30 In summary, increased MR activity in VSMCs leads to oxidative stress, proliferation, vascular remodelling and/ or calcification and has an important role in blood pressure control. 29 A role for miR-34b/C has been established for aldosterone-mediated VSMC calcification.…”
Section: Mr Activation In Vascular Smooth Muscle Cells (Vsmcs) Incrmentioning
confidence: 99%
See 1 more Smart Citation
“…23 MR activation has been shown to promote the expression of genes involved in MR-dependent vascular remodelling and calcification in VSMCs, such as collagens I and III, the integrin alpha-5 subunit, IL-16 and cytotoxic T-lymphocyte antigen-4 for vascular remodelling and genes associated with vascular calcification, such as alkaline phosphatase, parathyroid hormone receptor-2 and bone morphogenetic protein-2. 30 In summary, increased MR activity in VSMCs leads to oxidative stress, proliferation, vascular remodelling and/ or calcification and has an important role in blood pressure control. 29 A role for miR-34b/C has been established for aldosterone-mediated VSMC calcification.…”
Section: Mr Activation In Vascular Smooth Muscle Cells (Vsmcs) Incrmentioning
confidence: 99%
“…29 A role for miR-34b/C has been established for aldosterone-mediated VSMC calcification. 30 In summary, increased MR activity in VSMCs leads to oxidative stress, proliferation, vascular remodelling and/ or calcification and has an important role in blood pressure control.…”
Section: Mr Activation In Vascular Smooth Muscle Cells (Vsmcs) Incrmentioning
confidence: 99%
“…Mutations, deletions, translocations, and mutual regulation abnormalities of miRNAs can lead to the abnormal expression of related genes involved in the regulation of cancer development (Jinek & Doudna, 2009). Research has shown that SATB2 is regulated by many different miRNAs, such as miR-31 (Luo et al, 2016), miR-211 (Jiang et al, 2015), miR-27a (Gong, Lu, Yu, & Yu, 2016), miR-182 (Yang et al, 2014), and miR-34b/c (Hao, Zhang, Cong, Ren, & Hao, 2016). Previous studies into miR-34a found that it is expressed at a low level in a variety of human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%